VW performance improvement in the US - Weber, Christian (2015)
Volkswagen of America has a low market share of 2.2 % in 2014 in the US auto industry. Sales figures decrease in almost all product categories and the CEO of the Volkswagen Group of America is under pressure because he fails to achieve sales targets.